Ecological notes on the ecology of Thecadactylus solimoensis (Squamata, Phyllodactylidae) from Peruvian Amazon - Jordán, Juan C. (2011)
Thecadactylus solimoensis is an abundant nocturnal gekkonid species in Peruvian Amazonia. However, basic aspects on its ecology remain unknown. Here, we present data on diet, morphology, reproduction and nematode parasitism assessed in museum specimens.